PENGUATAN UMKM MELALUI DIGITALISASI KEUANGAN: IMPLEMENTASI APLIKASI SI APIK KEPADA PELAKU UMKM DI KOTA BALIKPAPAN PROVINSI KALIMANTAN TIMUR - Harianto, Rudy Pudjut; Asriandi, Asriandi; Saputra, Bambang; Lestari, Ani Linda (Jurnal Abdi Insani, 2025)
MSMEs play a vital role in the regional economy, but still face challenges in financial recording, digital literacy, and access to financing. This community service program aims to improve MSME capacity through the implementation of the SI APIK application. Activities include outreach, training, mentoring, and evaluation, involving MSMEs in Balikpapan City. The implementation method consists of five stages: outreach, training, mentoring, evaluation, and the development of a sustainability plan. A total of 10 MSMEs in Balikpapan City participated in this program, with a focus on improving digital financial literacy and consistent business transaction recording. Evaluation was conducted through direct observation, questionnaires, and analysis of application usage consistency. The questionnaire results showed that 90% of participants understood the training material, while after the mentoring phase, there was a 70% increase in application-based financial recording practices. This demonstrates that the use of technology can overcome the limited understanding of accounting in MSMEs while encouraging regularity in financial recording. Furthermore, the established success indicators, such as recording financial transactions at a minimum of 80%, participants' ability to operate the application independently up to 90%, preparation of monthly financial reports, and the formation of internal trainers, are starting to be achieved. Thus, the implementation of SI APIK not only provides practical benefits for MSMEs but also supports sustainable development goals by continuously increasing the capacity of small businesses.